2022
DOI: 10.1097/ajp.0000000000001055
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Effect of Adding Ketamine Versus Dexmedetomidine to Bupivacaine in Pecs-ⅠⅠ Block on Postoperative Pain Control in Patients Undergoing Breast Surgery

Abstract: Background: Pectoralis and serratus plane blocks (Pecs-II block) has successfully demonstrated a good quality of perioperative analgesia for breast surgery.Objective: This study aimed to compare the quality of postoperative pain control when adding either ketamine or dexmedetomidine to bupivacaine 0.25% for Pecs-II block.Methods: This prospective randomized double-blind study was conducted on 159 female patients with American Society of Anesthesiologist (ASA) physical status class I-III scheduled to have modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Based on the results of Yazigi et al, no reduction in acute pain score and supplemental morphine consumption following thoracotomy was observed in patients receiving the combination of ketamine and intercostal block ( 21 ). In contrast to the results of the present study, Hefni et al showed that the addition of dexmedetomidine to bupivacaine provides more effective postoperative analgesia than the addition of ketamine during pectoralis blocks in breast cancer surgery ( 22 ). However, in another study, adding 1 mg/kg of ketamine to 0.25% bupivacaine in an intercostal block in breast cancer surgery was shown to be useful, consistent with the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on the results of Yazigi et al, no reduction in acute pain score and supplemental morphine consumption following thoracotomy was observed in patients receiving the combination of ketamine and intercostal block ( 21 ). In contrast to the results of the present study, Hefni et al showed that the addition of dexmedetomidine to bupivacaine provides more effective postoperative analgesia than the addition of ketamine during pectoralis blocks in breast cancer surgery ( 22 ). However, in another study, adding 1 mg/kg of ketamine to 0.25% bupivacaine in an intercostal block in breast cancer surgery was shown to be useful, consistent with the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…This study selection process is summarized in the PRISMA flow chart ( Figure 1 ). According to Cochrane’s Risk of Bias 2 (RoB2) assessment, seventeen RCTs [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] were considered to be low-risk and three RCTs [ 30 , 31 , 32 ] had some concerns. Moreover, the quality of the included studies is summarized in Supplementary Materials (Table S2) .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies into breast cancer surgery reported on 24 h postoperative morphine consumption [ 13 , 16 , 18 , 21 , 31 ]. The meta-analysis of those studies concluded that total 24 h morphine consumption in the dexmedetomidine group was lower than that of the control group (SMD = −1.99 [95% CI −3.01 to −0.98], p = 0.0001, I2 = 91%, random effects) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We supposed that ketamine addition to the dexamethasone bupivacaine combination would induce the same effect if bupivacaine was used alone. A previous study [9] reported an increase in analgesia duration of 5.2 h by adding ketamine to the LA, with a pooled standard deviation of 2.8. Based on these findings, 29 patients in each group were required to reject the null hypothesis at an alpha level of 0.05 and a power of 80%.…”
Section: Sample Sizementioning
confidence: 87%